2020
DOI: 10.1021/acsomega.0c01444
|View full text |Cite
|
Sign up to set email alerts
|

Shaking-Induced Aggregation and Flotation in Immunoglobulin Dispersions: Differences between Water and Water–Ethanol Mixtures

Abstract: Structural characterization by three complementary methods of laser diagnostics (dynamic light scattering, laser phase microscopy, and laser polarimetric scatterometry) has established that shaking of immunoglobulin G (IgG) dispersions in water and ethanol–water mixtures (36.7 vol %) results in two effects. First, it intensifies the aggregation of IgG macromolecules. Second, it generates bubbles with a size range that is different in each solvent. The aggregation is enhanced in ethanol–water mixtures because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 41 publications
1
51
0
9
Order By: Relevance
“…1) There seem to be no any differences between the composition of solutions at very low concentrations (with ultrahigh dilution of the starting substance up to 10 24 times) and water prepared using a similar dilution technique (control water) as the starting substance is no longer found in solutions with very low concentrations. However, as shown in the study [16] where the starting solution contains a protein component, the concentration of the starting components in the solution obtained by serial dilution might not correlate with the estimated concentrations due to flotation. Such solutions may contain residual amounts (traces) of baseline proteins that may become denatured due to dilutions with intensive succussion.…”
Section: Discussionmentioning
confidence: 80%
“…1) There seem to be no any differences between the composition of solutions at very low concentrations (with ultrahigh dilution of the starting substance up to 10 24 times) and water prepared using a similar dilution technique (control water) as the starting substance is no longer found in solutions with very low concentrations. However, as shown in the study [16] where the starting solution contains a protein component, the concentration of the starting components in the solution obtained by serial dilution might not correlate with the estimated concentrations due to flotation. Such solutions may contain residual amounts (traces) of baseline proteins that may become denatured due to dilutions with intensive succussion.…”
Section: Discussionmentioning
confidence: 80%
“…The rationale for this work lies in the published results that have characterized the solutions of HD Abs as a self-organizing dispersed system in which nano-scale objects are generated [55]. It was demonstrated that solution of the HD Abs may contain aggregates of original Abs with gas nanobubbles which survived after multiple dilutions due to the flotation effect [44]. These results are in line with the previously shown presence of nanoparticles of the starting material even at a very high dilution level [56].…”
Section: Discussionmentioning
confidence: 99%
“…First, lactose has changed its physicochemical properties, for example, its conformation, as described in [61] in the process of saturation with highly diluted antibodies (specifically, since such a solution differs from a solution for saturation control). Second, it is reasonable to assume that nanoscale objects based on technologically processed (during dilution and vibration exposure) molecules of the original antibodies are present in the highly diluted antibody solution used for lactose saturation [44]. Apparently, lactose can accumulate these objects during saturation and release them during dissolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we studied water samples subjected to intensive shaking on a Vortex MSV-3500 vibrating platform at a frequency of 20 Hz for one minute. These studies were motivated by the results of References [36,37], where it was shown that shaking leads to an increase in the volume number density of nanobubbles by about 10 times. However, after shaking and settling for a certain time, the original properties of water should be restored.…”
Section: The Role Of Shakingmentioning
confidence: 98%